A prezygotic transmission distorter acting equally in female and male zebra finches Taeniopygia guttata. Issue 15 (17th July 2015) - Knief, Ulrich; Schielzeth, Holger; Ellegren, Hans; Kempenaers, Bart; Forstmeier, Wolfgang
Abstract The two parental alleles at a specific locus are usually inherited with equal probability to the offspring. However, at least three processes can lead to an apparent departure from fair segregation: early viability selection, biased gene conversion and various kinds of segregation distortion. Here, we conduct a genome‐wide scan for transmission distortion in a captive population of zebra finches (Taeniopygia guttata) using 1302 single‐nucleotide polymorphisms (SNPs) followed by confirmatory analyses on independent samples from the same population. In the initial genome‐wide scan, we found significant distortion at three linked loci on chromosome Tgu2 and we were able to replicate this finding in each of two follow‐up data sets [overall transmission ratio = 0.567 (95% CI = 0.536–0.600), based on 1101 informative meioses]. Although the driving allele was preferentially transmitted by both heterozygous females [ratio = 0.560 (95% CI = 0.519–0.603)] and heterozygous males [ratio = 0.575 (95% CI = 0.531–0.623)], we could rule out postzygotic viability selection and biased gene conversion as possible mechanisms. Early postzygotic viability selection is unlikely, because it would result in eggs with no visible embryo and hence no opportunity for genotyping, and we confirmed that both females and males heterozygous for the driving allele did not produce a larger proportion of such eggs than homozygous birds. Biased gene conversion is expected to be rather localized, while we could trace transmission distortion in haplotypes of several megabases in a recombination desert. Thus, we here report the rare case of a prezygotically active transmission distorter operating equally effectively in female and male meioses.